Pendidikan untuk Perempuan : Kesetaraan Gender - Rinanda Ramadhani; Cut Kumala Sari; Nurul Faizah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The main method to encourage women to achieve gender equality is education. Women have greater opportunities to improve their quality of life, fight for their rights, and actively participate in various aspects of life through education. However, social reality shows that women still face various challenges, such as unequal access to education, patriarchal cultural construction, and limited roles in the public sphere. In this article, the importance of education as a way to encourage women to achieve fair gender equality is discussed. Education not only teaches women what they need to know, but also gives them a critical understanding of their roles and potential. In this context, education must be designed inclusively and responsive to the needs of women, taking into account the social, cultural, and historical aspects that affect their lives. Women's education is essential to building a just, equal, and sustainable society because achieving gender equality in education is not just an individual effort; it also requires systemic support from policies, curricula, and a supportive social environment.